Prevent Devastating Hail Storms, Flash Floods, Tornadoes, Tsunami, by Eradicating Global Abortion, and Reversing Contraception: A Retrospective Analysis - Elizabeth JeyaVardhini Samuel (Highlights on Medicine and Medical Science Vol. 3, 2021)
Back ground: The period of contraception and abortion [mid-twentieth and early-twentieth centuries] saw a rise in the frequency of hail storms, tornadoes, flash floods, and tsunamis; as a result, an altruistic analysis of any link between increasing natural disaster trends and contraception, abortion, was planned for the past 4-5 decades, by analysing the environmental pollutant. Methods: The occurrence of hail storms, flash floods, tornadoes, and tsunami, was timed with the gradual and stealthy implementation of global contraception and abortion. Environmental pollutants, including as estrogen, alpha feto [1] protein, and beta human chorionic gonadotropin, were measured in rivers and oceans and associated with the results. Three samples of river water around Cape Comorian were tested for Estrogen, as were four samples of sea water from four distinct seas: Indian Ocean, Arabian Sea, Bay of Bengal near cape, and Bay of Bengal near Union Territory. Estimation of Fetal, adult hemoglobin in sea water was attempted by routine hemoglobin electrophoresis. Estimation of alpha feto protein and \(β\) Human chorionic gonado tropin in river and sea water was undertaken Results: Over the last 4-5 decades, there has been a 2.5-fold rise in hail storms, flash floods, tornadoes, [p<0.01] , and a 6-fold rise [p <0.0005] in tsunami. Earlier estimates [1] of estrogen, alpha feto protein, beta human chorionic gonado tropin in rivers, oceans showed their presence as follows Estrogen was detected in river water- 3-5pg/ml and sea water - 0.3-1pg/ml. Alpha feto protein was detected in sea, river water as <0.6ng/ml, \(β\) human chorionic gonado tropin was detected in sea and river water as <0.1miu/ml confirming further, aborted blood pollution of the sea, river. It was also in the rivers, which were diluted in the oceans. Hemoglobin could not be detected in water samples since the technology could only detect in grams, but oestrogen could only be estimated in pg. Conclusion: Contraceptive menstrual blood pollution, or aborted blood pollution of the waterways, as demonstrated by estrogen, alpha fetoprotein, and beta human chorionic gonadotropin, depletes oxygen in rivers and oceans, which cannot be replaced by plants depleting ozone, combined with putrefaction of enormous fetuses [2] producing toxic, inflammable, explosive gases, resulting in increased trends of tornadoes, flash floods, hail storms, tsunamis.